REORGANIZATION OF GENERA WITHIN TRIBE INGEAE OF THE MIMOSOID LEGUMINOSAE - Robert H Mohlenbrock (BRIN Publishing (Penerbit BRIN), 1963)
Members of Tribe Ingeae of the mimosoid Leguminosae are characterized by their numerous, indefinite stamens which are connate for a portion of their length. Flower structure within the tribe is essentially uniform. The calyx is generally 5-lobed and cupular or tubular. The corolla likewise is usually 5-lobed and tubular. The ovaries vary from one to fifteen per flower, although unicarpelly predominates. Leaves are usually bipinnate, although once-pinnate leaves occur in a few species